Radioactive Mineral Distribution on Tin Placer Deposits of Southeast Asia Tin Belt Granite in Bangka Island - Ngadenin, Ngadenin; Sukadana, I Gde; Muhammad, Adi Gunawan; Indrastomo, Frederikus Dian; Rosianna, Ilsa; Ciputra, Roni Cahya; Adimedha, Tyto Baskara; Pratiwi, Fadiah; Rachael, Yoshi (BRIN Publishing, 2023)
Bangka Island is an area rich in primary and secondary tin deposits. Tin deposits are formed around the contact between granite and older rocks, while secondary tin deposits are formed in the modern channels and paleochannels. Many previous researchers have researched radioactive minerals in primary tin deposits and modern channel deposits, but research on radioactive minerals in paleo channel deposits has never been carried out. The characterization of radioactive minerals in paleo channel deposits was done in this study to determine the potency of radioactive minerals in secondary tin deposits by comparing the content of radioactive minerals in paleochannels with modern channels and tin mine tailing deposits. The data used were mineralogical data and radioactivity data, along with the uranium and thorium content of the rocks from several previous studies. Data showed significant mineral content differences in paleo channel, modern channel, and tin mine tailings deposits. Mineral (monazite and zircon) content in tin mine tailing deposits was the highest. Source rocks for the radioactive minerals monazite and zircon are predicted to be the granitic rocks or tourmaline quartz veins of primary tin deposits. The radioactivity value of rocks in the paleo channel is relatively the same as the modern channel, ranging from 20 to 150 c/s. Uranium content in paleo channel is the same as modern channel deposits, ranging from 10 to 15 ppm eU. The thorium content of the rocks in the paleo channel ranges from 1 to 60 ppm eTh, while in the modern channel, it ranges from 1 to 45 ppm eTh. The radioactivity value and uranium content of the rocks are less effective for determining potential areas of radioactive minerals in placer tin deposits. In contrast, data on thorium content are quite effective for determining potential areas of radioactive minerals in placer tin deposits.